Draft Annual Plan 1983-84 Himachal Pradesh - Planning Commission (Planning Commission, 1983)
Agriculture commands a dominating position in the economy of Himachal Pradesh. But at the same time, it has consistently remained the Achille’s heel in our economy as well as that of the nation. This fact becomes the strongest determinant of overall economic growth because agriculture sector accounts for about 50 per cent of the net SDP/GNP. The data on the movement of agriculture contribution to net SDP at constant prices have been depicted in the following table
Planning Department, Himachal Pradesh